EXTRACTION AND PURIFICATION OF CASTOR OIL FROM CASTOR SEEDS TO STUDY ITS NUTRITIONAL AND BIOMEDICAL IMPORTANCE (The Research of Medical Science Review, 2025)
Castor oil, derived from the seeds of Ricinus communis, is a versatile natural product with significant nutritional and biomedical importance. This study focuses on the extraction and purification of castor oil to evaluate its physicochemical properties and potential applications. The oil was extracted using a cold-press method to retain its bioactive components, followed by purification to remove impurities and enhance its quality. The nutritional profile of castor oil, rich in ricinoleic acid, essential fatty acids, and antioxidants, was analyzed to explore its health benefits, including its roles in boosting immunity, improving skin health, and aiding digestion. Additionally, its biomedical applications, such as its use as a bio-lubricant, drug carrier, and wound- healing agent, were investigated. This research highlights the significance of castor oil in pharmaceutical formulations and as a sustainable alternative to synthetic compounds. The study also addresses the challenges of large-scale production, storage stability, and standardization of quality parameters. Prospects involve optimizing extraction techniques to enhance yield and exploring their potential in developing advanced biomedical materials. This work contributes to the growing interest in natural products as eco-friendly and multifunctional resources for health and industry.